Dominasi Pertumbuhan HHBK Di Desa Waesala Kecamatan Huamual Belakang Kabupaten Seram Bagian Barat - Pietersz, Juglans Howard (Tropical Small Island Agriculture Management, 2025)
This study aims to identify the potential and dominance patterns of Non-Timber Forest Products (NTFP) species in the Waesala Village Forest Area, Huamual Belakang District, West Seram Regency. Based on the research results, this area has NTFP potential from four main families, namely Arecaceae, Myrtaceae, Annonaceae, and Fabaceae. Among these species, Melaleuca cajuputi is absolutely dominant with an Important Value Index (IVI) of 162.3% at the tree level, 181.9% at the pole level, 143.9% at the stake level, and 168.5% at the seedling level. The species diversity (H’) in this area is classified as low, with the highest value at the tree level (H’ = 0.4669) and the lowest at the seedling level (H’ = 0.2644). This indicates that natural regeneration of other species is very limited due to the dominance of Melaleuca cajuputi. The distribution of individuals among species (E) is most even at the pole stage (E = 0.3186), while the seedling stage has the lowest evenness (E = 0.1907), emphasizing the dominance of a single species at this stage. The dominance index (C) shows the highest value at the seedling stage (C = 0.718), indicating the absolute dominance of Melaleuca cajuputi during this phase, with lower values at the stake stage (C = 0.535), pole stage (C = 0.443), and tree stage (C = 0.364). Several factors contribute to the dominance of Melaleuca cajuputi, including rapid regeneration ability, effective dispersal, adaptation to extreme environmental conditions, as well as human intervention through land-burning practices by cajuput oil farmers.